Hydroxytyrosol induces phase II detoxifying enzyme expression and effectively protects dopaminergic cells against dopamine- and 6-hydroxydopamine induced cytotoxicity. (June 2016) - Yu, Guohua; Deng, Ajun; Tang, Wanbin; Ma, Junzhi; Yuan, Chonggang; Ma, Jiyan
Abstract: Parkinson's disease (PD) is the second most common late-age onset neurodegenerative disease. Except for the symptomatic alleviating treatment, no disease modifying therapy is currently available. In this study, we investigated the potential neuroprotective role of hydroxytyrosol (HT), a major phenolic compound present in olive oil, against dopaminergic cell death. We found that HT effectively protected dopaminergic SH-SY5Y cells against dopamine (DA) and 6-hydroxydopamine (6-OHDA) induced cell death, but had no apparent effect on 1-methyl-4-phenylpyridinium (MPP + )-induced cytotoxicity. Furthermore, we have shown that HT efficiently induced the expression of phase II detoxifying enzymes, including NAD(P)H quinone oxidoreductase 1 (NQO1). Using an NQO1 inhibitor, we revealed that increased NQO1 expression contributed to the protective effect of HT against dopaminergic cell death. Together, our findings suggest that HT has a protective effect against DA- and 6-OHDA-induced dopaminergic cell death, supporting the beneficial effect of olive oil in preventing DA-metabolism related dopaminergic neuron dysfunction. Highlights: Hydroxytyrosol (HT) protects SH-SY5Y cells from DA and 6-OHDA induced cell death. HT pretreatment has no effect on MPP + -induced cell death. HT treatment increases the expression of several phase II enzymes. NQO1 contributed to the protective effect of HT against dopaminergic cell death.